STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA SI BOKO DI NAGARI SUNGAI PISANG KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Faiska, Alodia; Nurizzati, Nurizzati (Universitas Negeri Padang, 2019)
This study aims to describe: (1) the social structure and function of the folklore of the Si Boko legend in Nagari Sungai Pisang Bungus Bay Kabung Subdistrict, Padang City, (2) the social function of the Si Boko folklore legend in Nagari Sungai Pisang Bungus Subdistrict Teluk Kabung Kota Padang. This research is a qualitative study using descriptive methods. The data of this research are the folklore of Si Boko's legend in Nagari Sungai Pisang, Bungus Bay, Teluk Kabung District, Padang City. Data was collected from informants through recording techniques, interviews, and observations. The data that has been collected is then analyzed with several stages: (1) data identification stage; (2) data classification or analysis stage; (3) the stage of discussion and conclusion of the results of classification or data analysis; and (4) reporting phase.